Biomechanical Aspects of Actin Bundle Dynamics - Lange, Julia; Bernitt, Erik; Döbereiner, Hans-Günther (Frontiers in Cell and Developmental Biology, 2020)
Lamellipodial and filopodial protrusions are two of the main aggregate types of filamentous actin in living cells. Even though filopodia are essential to a range of vital cell functions, the mechanisms leading to their formation are still debated. Filopodia are relatively stiff and rod-like structures that are embedded in the highly dynamic framework of the backward flowing meshwork of the lamellipodium. Phenomena such as lateral filopodia drift and collision events suggest that mechanical aspects play a significant role in filopodia dynamics. In this paper, we systematically analyze the interplay between the backward flow of actin in the lamellipodium and the drift velocity \textcolor{red}{of actin bundles, that we identify to be filopodia,} in a quantitative manner in cells of given morphology and controlled myosin activity. Moreover, we study mechanical aspects of fusion of \textcolor{red}{actin bundles} drifting laterally in the lamellipodium. We find that the dynamics of \textcolor{red}{actin bundles} drift and fusion can be captured in a mechanical framework, which leads to a model of \textcolor{red}{actin bundles} orientation.